European physico-theology (1650-c.1760) in context celebrating nature and creation - Greyerz, Kaspar von 1947- (Oxford-Warburg studies, 2022)
Physico-theology celebrated the observation of nature as a way toward recognising God as Creator, demonstrating the compatibility of the biblical record with new science. This is an English-language monograph which studies the impact of physico-theology on the intellectual and socio-cultural establishment in Europe from the mid-17th century